Harmful Algal Blooms in Malaysian Waters - Lim, Po Teen; Gires, Usup; Leaw, Chui-Pin (Sains Malaysiana 41, 2012)
Harmful algal blooms (HABs) events have been increasingly reported in the country, not only of the frequency and severity of the events, but also involved more species than previously known. In this paper, a decadal review of HABs events in Malaysia is summarized. Bloom events caused by harmful dinoflagellate species including the shellfish poisoning events were highlighted. Paralytic shellfish poisoning (PSP) is no longer restricted to Sabah coasts and Pyrodnium bahamense. Bloom of Alexandrium minutum was reported for the first time in the Peninsula with six persons hospitalized including one casualty after consuming the contaminated benthic clams. Algal blooms that are associated with incidence of massive fish kills have been reported from both east and west coasts of the Peninsula in conjunction to finfish mariculture loses. The culprits of these bloom events have been identified as the dinoflagellates, Cochlodinium polykrikoides, Neoceratium furca, Prorocentrum minimum, Noctiluca scintillans and a raphidophyte, Chatonella ovata. In this paper, some of these HABs species were characterized morphologically and genetically, including their toxicity. Therefore, with the increase of coastal utilization and eutrophication, prevention, management and mitigation strategies, such as site selection, moving pens, clay spraying should be adopted to minimize the impact of these natural events.